Love at first - Clayborn, Kate (Kensington Publishing Corp., 2021)
"Sixteen years ago, a teenaged Will Sterling saw - or rather, heard - the girl of his dreams. Standing beneath an apartment building balcony, he shared a perfect moment with a lovely, warm-voiced stranger. It's a memory that's never faded, though he's put so much of his past behind him. Now an unexpected inheritance has brought Will back to that same address, where he plans to offload his new property and get back to his regular life as an overworked doctor. Instead, he encounters a woman, two balconies above, who's uncannily familiar... No matter how surprised Nora Clarke is by her reaction to handsome, curious Will, or the whispered pre-dawn conversations they share, she won't let his plans ruin her quirky, close-knit building. Bound by her loyalty to her adored grandmother, she sets out to foil his efforts with a little light sabotage. But beneath the surface of their feud is an undeniable connection. A balcony, a star-crossed couple, a fateful meeting - maybe it's the kind of story that can't work out in the end. Or maybe, it's the perfect second chance..." -- Amazon.